1. W podanym wyrażeniu wykonaj redukcję wyrazów podobnych, a następnie oblicz wartość tego wyrażenia dla x= 3.

9 —­­ x­² + 5x ­­­­­­­­­— 12 —­­ 3x³ + 2x

2. W podanym wyrażeniu wykonaj redukcję wyrazów podobnych, a następnie oblicz wartość tego wyrażenia dla x= ­­­­­­­­­­­­­­—4 i y= ­­­­­­­¼ .

—­­3xy —­ 2,5x­² + 4,3xy + 6y­² + 6,5x­² + 0,5y­²

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-04T17:58:46+01:00
9 —­­ x­² + 5x ­­­­­­­­­— 12 —­­ 3x³ + 2x = -3 - 4x² + 7x
-3 ×
2 1 2
2010-03-04T18:08:11+01:00
1
9 —­­ x­² + 5x ­­­­­­­­­— 12 —­­ 3x³ + 2x
-3-4x²+7x
x=3
-3-4*9+7*9=-3-36+63=-24
2
1,3xy+4x²+6,5y²
x=-4 y=¼
1,3*(-4)*¼+4*(-4)²+6,5*¼²=
=-1,3+64+6,5*1/16=
=62,7*13/32=815,1/32
2 1 2